Functional, Antioxidant, and Anti-Inflammatory Properties of Cricket Protein Concentrate (Gryllus assimilis) - María Fernanda Quinteros; Jenny Martínez; Alejandra Barrionuevo; Marcelo Rojas; Wilman Carrillo (Biology, 2022)
Edible insects can represent an alternative to obtain high-quality proteins with positive biological properties for human consumption. Cricket flour (Gryllus assimilis) was used to obtain cricket protein concentrate (CPC) using pHs (10.0 and 12.0) of extraction and pHs (3.0, 4.0, 5.0, and 6.0) of isoelectric precipitation (pI). Protein content, water and oil absorption capacity, protein solubility, antioxidant, and anti-inflammatory activities were determined. In addition, the protein profile was characterized by electrophoresis and the in vitro CPC digestibility was evaluated. Cricket flour presented 45.75% of protein content and CPC 12–5.0 presented a value of 71.16% protein content using the Dumas method. All samples were more soluble at pH 9.0 and 12.0. CPC 12–3.0 presented a percentage of water-binding capacity (WBC) of 41.25%. CPC 12–6.0 presented a percentage of oil-binding capacity (OBC) of 72.93%. All samples presented a high antioxidant and anti-inflammatory activity. CPC 12–4.0 presented a value FRAP of 70,034 umol trolox equivalents (TE)/g CPC, CPC 12–6.0 presented a value ABTS of 124,300 umol TE/g CPC and CPC 10–3.0 presented a DPPH value of 68,009 umol TE/g CPC. CPC 10–6.0 and CPC 12–6.0 presented high anti-inflammatory activity, with values of 93.55% and 93.15% of protection, respectively. CPCs can be used as functional ingredients in the food industry for their excellent functional and biological properties.